From the Struggles for the Nemagon to the Murder of Jairo Mora Sandoval: Reflections on Culture of Protest (Revista Rupturas, 2018)
This paper shows a discussion about Costa Rican culture of protest, on a basis of a case study of manifestations carried out by workers affected by DBCP, pesticide known as Nemagon, and protests helded in memory of Jairo Mora Sandoval, environmentalist who was murdered in 2013. This paper draws a discussion about how culture of protest might promoteimpunity.
Keywords: Social protest; justice; impunity; pesticides; Jairo Mora Sandoval